Ultrasonic Activation of Thermally Sensitive Liposomes - Mylonopoulou, E; Arvanitis, C; Bazan-Peregrino, M; Arora, M; Coussios, C (2010)
Cancerous cells are known to be more vulnerable to mild hyperthermia than healthy cells, which can survive temperatures above 43°C for brief periods of time. Currently in phase III clinical trials for liver cancer, ThermoDox® (Celsion Corporation) is a drug delivery system containing doxorubicin, a common anti-cancer agent, encapsulated within a thermally sensitive liposome designed to release its contents above 39.5°C. Activation of such an agent with the use of HIFU, which can generate localized heating non-invasively, would combine the benefits of targeted chemotherapy and hyperthermia while minimizing undesirable systemic side-effects. To that end, the resolution and reliability with which HIFU-induced hyperthermia can achieve Thermodox® release was investigated using a novel agar-based gel embedding liposomes at clinically relevant concentrations (0.02 mg/ml). The gel was exposed to 1.15 MHz HIFU (Sonic Concepts H102) using a range of clinically relevant pressure amplitudes (0-6 MPa peak rarefactional), duty cycles (10-100%) and exposure durations to identify optimal insonation conditions for complete doxorubicin release. The corresponding temperature profiles were mapped with 0.5 mm spatial resolution using an embedded needle thermocouple; drug release was quantified using fluorimetry. Complete release over the HIFU focal area was obtained for 6-s continuous wave exposure at 5.2 MPa peak rarefactional pressure, i.e. under exposure conditions for which the temperature exceeded 43°C throughout the focal volume. For a given HIFU energy input, both the final temperature reached and the rate of heating were found to affect release significantly. However, ThermoDox® release was achieved only due to thermal effects of HIFU, and not by other ultrasound effects, such as cavitation without heating, showing robustness of HIFU-induced hyperthermia as a release mechanism. © 2010 American Institute of Physics.